(untitled) (JS (JURNAL SEKOLAH), 2019)
Abstract: Increased Interest in Learning Subject Sanitation, Hygiene and Safety Through Discovery Methods. Sanitation, hygiene and work safety are one of the productive subjects that are very important in supporting the field of culinary expertise. For this reason, the need for more creative methods or methods in delivering each of the basic competencies presented, especially cleaning materials and sanitary materials to increase the interest of these students. From the results of observations in the first and second cycles the results obtained 50% cycle I completeness of students, while the second cycle 94.11% completeness of students. Here an increase of 44.11% students completeness. The use of discovery methods can be carried out continuously to get maximum results. Keywords: interest, sanitation hygiene and safety, discovery method Abstrak: Peningkatan Minat Belajar Mapel Sanitasi, Hygiene dan Keselamatan Kerja Melalui Metode Discovery. Sanitasi, hygiene dan keselamatan kerja adalah salah satu mata pelajaran produktif yang sangat penting dalam menunjang bidang keahlian tata boga. Untuk itu perlunya metode atau cara yang lebih kreatif dalam penyampaian setiap kompetensi dasar yang disajikan, terutama bahan pembersih dan bahan saniter untuk meningkatkan minat dari siswa tersebut. Dari hasil observasi pada siklus I dan II diperoleh hasil 50 % siklus I ketuntasan siswa, sesangkan siklus II 94.11 % ketuntasan siswa. Disini terjadi peningkatan sebesar 44.11 % ketuntasan siswa.Penggunaan metode discovery bisa dilaksanakan secara berkesinambungan untuk mendapatkan hasil yang maksimal. Kata Kunci: minat, sanitasi hygiene dan keselamatn kerja , metode discovery